Stress and midlife women's health - Lynnette Leidy Sievert; Nicole Jaff; Nancy Fugate Woods (BMC, 2018)
Abstract Stress is ubiquitous in everyday life, and chronic stress can have negative consequences for health and social welfare. Although a growing body of research addresses the relationships between stress, health, and quality of life, there is a gap in the literature with regard to the effects of stress among women at midlife. The purpose of this commentary is to provide a brief history of stress research, including various methods for measuring stress; discuss the physiological effects of stress; and review relevant studies about women at midlife in order to identify unanswered questions about stress. This commentary also serves as an introduction to a thematic series on stress and women's midlife health where stress is examined in relation to a wide range of symptom experiences, in the context of family and negative life events, as associated with women's work, and correlated with the challenges of violence and discrimination. The goal of this commentary and thematic series is to extend the conversation about stress to include women at midlife, and to examine where we are, and where we are going, in order to direct future research and provide relevant care for this growing population.